1980
DOI: 10.1093/infdis/141.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evidence of Intestinal Colonization by Clostridium botulinum in Four Cases of Infant Botulism

Abstract: Infant botulism is an infectious form of a disease heretofore principally known as food-borne intoxication. Previous epidemiologic and laboratory studies have shown that infant botulism results from the ingestion of spores of Clostridium botulinum that subsequently germinate in the infant intestine and produce botulinal toxin. A quantitative study of the fecal microflora of four infants with infant botulism revealed the presence of C. botulinum in numbers as high as 6.0 x 10(8) colony-forming units (cfu)/g. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…Dentre essas, seis amostras tinham sido fornecidas a bebês, que desenvolveram a doença. WILCKE et al (1980) avaliaram a microbiota fecal de quatro crianças com botulismo infantil, revelando a presença de Clostridium botulinum.…”
Section: Ciência Rural V38 N2 Mar-abr 2008unclassified
“…Dentre essas, seis amostras tinham sido fornecidas a bebês, que desenvolveram a doença. WILCKE et al (1980) avaliaram a microbiota fecal de quatro crianças com botulismo infantil, revelando a presença de Clostridium botulinum.…”
Section: Ciência Rural V38 N2 Mar-abr 2008unclassified
“…Repeated purgation is unwarranted and potentially hazardous. Since it is not known whether the C. botulinum organisms that are present in feces in large numbers [about 107/g (38)] may be infectious for other infants or adults by fecal-oral transmission, it is recommended that the usual precautions against fecal bacterial pathogens be taken during hospitalization. As some patients ex crete C. botulinum toxin and organisms in their feces for weeks to months after they have returned home, the importance of careful hand washing and diaper disposal deserves emphasis.…”
Section: The Hospitalized Patientmentioning
confidence: 99%
“…Unlike most bacterial infections in which one species predomin ates, C. botulinum is just one of several clostridial and other anaerobic species present in the intestinal lumen of patients (38). Oral antibiotics that are clostridiocidal or clostridiostatic may be expected to alter the intestinal microecology in an unpredictable manner and might actually permit intesti nal overgrowth by C. botulinum.…”
Section: The Hospitalized Patientmentioning
confidence: 99%
“…However, a global survey found that Australia had one of the highest numbers of notified cases of infant botulism in the world (12,13). Infant botulism results from the ingestion of Clostridium botulinum spores which germinate and temporarily colonize the infant's colon, followed by growth of vegetative cells that produce BoNT (14)(15)(16). This form of the disease only occurs in infants, generally under 1 year old, as they have relatively low levels of gastric acid and poorly developed normal gut microflora (17).…”
mentioning
confidence: 99%